Moderasi Financial Attitude pada Financial Literacy dan Risk Tolerance terhadap Keputusan Investasi - Indiraswari, Susmita Dian; Setiyowati, Supami Wahyu (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
Investment decisions as a decision are called capital budgeting, which is the whole process of planning and making decisions regarding spending with a long-term payback period or more than one year). With the right investment decision, it is hoped that someone can minimize investment risk and maximize the expected rate of return. This study aims to determine the effect of moderating financial attitudes on financial literacy, and risk tolerance on investment decisions in college capital market study group students in Malang City. This research uses quantitative research methods. The population used in this study were students from the Capital Market Study Group, totaling 266 students from 7 (seven) universities in Malang City. The sampling technique uses saturated sampling. Data collection techniques using a questionnaire. The data analysis technique uses Partial Least Square (PLS). The urgency of this research is that it is important for the younger generation to invest early. The results of this study indicate that financial literacy and risk tolerance affect investment decisions. Financial attitude moderates financial literacy with investment decisions. Financial attitudes do not moderate the relationship between risk tolerance and investment decisions.